Community Psychology as a Process of Citizen Participation in Health Policy; Comment on "The Rise of Post-truth Populism in Pluralist Liberal Democracies: Challenges for Health Policy" - Danny Taggart (Kerman University of Medical Sciences, 2018)
This brief commentary discusses a recent paper by Speed and Mannion that explores "The Rise of post truth populism in liberal democracies: challenges for health policy." It considers their assertion that through meaningful democratic engagement in health policy, some of the risks brought about by an exclusionary populist politics can be mediated. With an overview of what participation means in modern healthcare policy and implementation, the field of community psychology is presented as one way to engage marginalized groups at risk of exploitation or exclusion by nativist populist policy.